Bioassessment of Sumberremis River based on macroinvertebrate communities in Sukorejo Village, Tirtoyudo Subdistrict, Malang Regency - Kartika, Octavia A.B. Chotimatus; Sri, Sudaryanti; Dini, Atikawati (Jurnal Pembangunan dan Alam Lestari, 2026)
The Sumberremis River, a tributary within the upper Brantas River basin, is increasingly subjected to ecological pressure driven by intensifying anthropogenic activities, including settlements, agriculture, and plantation expansion. These land-use dynamics elevate the risk of water quality degradation and threaten the integrity of aquatic biota. This study assesses the ecological status of the Sumberremis River using benthic macroinvertebrates as bioindicators, applying the SIGNAL2 (Stream Invertebrate Grade Number–Average Level) Index to quantify environmental conditions. Field sampling was conducted at six representative stations using a standardized kicking net method across 10 m riffle habitats. Collected specimens were identified to the family level to ensure consistency and comparability of bioassessment metrics. A total of 36 taxa were recorded, encompassing 10 orders and 6 classes, indicating moderate biodiversity across the study reach. Spatial variation was evident, with Station 6 exhibiting the highest taxonomic richness (21 taxa) and Station 1 the lowest (13 taxa), reflecting differing levels of environmental stress. SIGNAL2 scores ranged from 3.82 to 5.00, with the highest ecological quality observed at Station 6 and the lowest at Station 1. Based on the SIGNAL2 classification framework, the river is positioned within Quadrant 2, corresponding to a lightly polluted condition. This status suggests that while severe ecological degradation has not yet occurred, early signs of environmental disturbance are present, likely associated with diffuse organic inputs and land-based runoff. These findings highlight the need for proactive river management strategies, particularly the reduction of organic loading and improved control of non-point source pollution. Strengthening watershed governance and promoting sustainable land-use practices are critical to preventing further ecological decline and maintaining the functional integrity of the Sumberremis River system.